The Economics of Entrepreneurship: What We Know and What We Don't - Simon C. Parker (Max Planck Institute for Research into Economic Systems, 2005)
This introductory, non-technical, article offers a reflective overview of what Economics adds to our understanding of entrepreneurship. It is designed primarily to showcase to young entrepreneurship scholars several interesting research questions and a toolbox of methods to answer them. First, I will illustrate the kinds of questions that can be posed and answered using Economics. Then I will present and discuss a selective list of "canonical" theoretical and empirical models that form the intellectual bedrock of the Economics of Entrepreneurship. After that, I present and discuss some well-established theoretical contributions and empirical findings that have been generated by the approach. I conclude by discussing aspects of "What we don't know" and should. This part of the article identifies several ideal future trends in research that build on and complement the foundations of entrepreneurship that are delineated in the main body of the article.
Keywords: 330; Unternehmer; Theorie